Social Security, Demographic Trends, and the Federal Budget. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper considers the implications of the prospective aging of the U.S. population for the social security system and concludes that the large and growing cashflow surpluses of the social security trust funds should be saved to help insulate living stands against this change. A number of illustrative scenarios are presented in which the impact of pursuing this policy is analyzed within the context of a growth model incorporating the demographic projections of the Social Security Administration. If the current unified budget framework, which includes Social Security trust fund flows, is retained, the suggested policy would require that fiscal surpluses be achieved.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet